Generational Differences and Determinants of Purchase Behavior towards Sustainable Clothing in a Developing Economy - Valentin, Alvin Patrick M. (Archīum Ateneo, 2023)
The fashion industry contributes significant plastic pollution and greenhouse gas emissions globally. One approach to minimize the industry’s environmental impact is through a shift to sustainable clothing. This study determined the predictors of purchase behavior towards sustainable clothing in a developing economy, which is the Philippines. Furthermore, this paper compared Filipinos from Generations X and Z. Results of a multiple regression analysis from a sample of 212 participants in an online survey showed that generation and environmental knowledge predicted the purchase of sustainable clothing. Moreover, Gen Z scored higher in environmental knowledge and purchase of sustainable clothing. The findings provide insights on increasing the usage of sustainable clothing, which can significantly reduce the environmental impact of the fashion industry.